Representasi Kecerdasan Buatan Dalam Iklan Marjan Edisi 1446 Hijriah (Youtube Marjanbudoin) - Marchelino Argayoga Pradana; Anisti; Tuty Mutiah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Digital advertising has become a strategic promotional medium. Marjan, a renowned syrup brand, is known for its innovative ads, such as the 2025 Ramadan edition titled Bangkitnya Calon Arang. This advertisement highlights the issue of runaway artificial intelligence in the future, making it a compelling subject for study. The purpose of this research is to analyze the representation of artificial intelligence in the ad using Roland Barthes semiotic approach. Employing a descriptive qualitative method, data was collected through non-participant observation and visual documentation. The analysis results show that artificial intelligence is represented through two myths. Initially, artificial intelligence is depicted as a harbinger of civilizational progress, forming the myth of a future dominated by high technology. However, when it spirals out of control, the representation shifts to a destructive force, creating the myth of artificial intelligence as a ruler that robs humanity. The climax of the ad asserts the myth of humanity's victory over oppressive technology, symbolized by the power of a mother's prayer. In conclusion, Marjan's ad successfully presents a complex narrative about the potential of artificial intelligence while prioritizing the value of humanity.